"Straunge and Prodigious Miracles"? John Foxe's Reformation of Virgin Martyr Legends. Issue 2 (3rd July 2019) - Freeman, Thomas S.; Monta, Susannah Brietz
ABSTRACT: John Foxe's Actes and Monuments is generally regarded as an aggressively Protestant work. Yet in his discussion of virgin martyrs in the early Church, Foxe displays a reverence for their virginity and a reluctance to dismiss the often prodigious miracles attributed to them. Foxe made skeptical comments on many of the miracles, but he qualified these comments, leaving the truth to the judgement of his readers. Comparison of Foxe's accounts of these virgin martyrs with the accounts of them in the Magdeburg Centuries–an indispensable source for Foxe's history of the early Church–shows that Foxe frequently took a softer line on the virgin martyrs and their miracles than his Lutheran colleagues did. We suggest a number of reasons for this restraint. Importantly, the cause of Foxe's circumspection is not simply his personal convictions, or else he would not have articulated his reservations. Instead, his caution is a striking indication of the strength of religious conservatism in early modern England.